(untitled) (Research, Society and Development, 2022)
This article aims to assess the risk of falls related to the use of medication in patients of a public hospital service, before and after admission to the hospital service, in Teresina-PI. This is a cross-sectional and descriptive study, collecting data on age, sex, comorbidities and medications through the medication reconciliation form within a three-month interval. The sample consisted of 286 patients admitted to the medical and surgical inpatient units, with a mean age of 56.5 (± 17.81) years, with the predominant male gender. A greater number of prescription drugs aimed at the treatment of cardiovascular diseases was identified. The percentage of patients at risk of falling related to pharmacotherapy before admission was 21%, and at admission it increased to 36.7%. There was an association between age, polymedication, presence of possible drug interaction and having one or more comorbidities with the risk of falls related to the use of medication in hospitalized patients. The use of certain medications is recognized as an important and modifiable risk factor for falls. Therefore, the identification of patients who use these drugs is of fundamental importance to prevent the occurrence of this event, through preventive measures that take into account the drug therapy used.